UJI VALIDITAS DAN RELIABILITAS KUESIONER MODEL UTAUT UNTUK EVALUASI SISTEM PENDAFTARAN ONLINE RUMAH SAKIT - Tugiman Tugiman; Herman Herman; Anton Yudhana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Information technology used to improve hospital services, especially in patient registration services. This function is very useful during the new adaptation period to break down crowds in the registration queue and reduce the risk of transmission of covid 19, so many hospitals have developed an online registration system for outpatients. PKU Muhammadiyah Gombong Hospital has developed the SIPENDOL (Online Registration System) application which has been running since May 2020 and has never been evaluated. One of the basic instruments that can be used to evaluate technology acceptance is UTAUT (Unified Technology and Acceptance Use of Technology). UTAUT needs to be developed according to user requirements specifications regarding what technology will be evaluated. The development of the questionnaire needs to be tested for validity and reliability tests, aiming to determine the level of accuracy so that in the future the data will be widely used. The purpose of this study was to identify the validity and reliability of the questionnaire based on the UTAUT model on the dimensions of Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Conditions to evaluate the use of online registration in hospitals. Questionnaires were distributed to 30 online registration users at PKU Muhammadiyah Gombong Hospital. The results of the questionnaire were analyzed using SPSS software. The results of the validity test using the Pearson product moment were declared to be 100% valid (r-count > r-table). The results of the reliability test were declared reliable because the value of the reliability coefficient (cronbach's alpha) was 0.905 > 0.361. Therefore, this questionnaire is recommended as an instrument to evaluate patient acceptance of online registration technology in hospitals based on the UTAUT model.